1493. The Incremental Burden of Nontuberculous Mycobacterial Lung Disease (NTMLD) among Patients with chronic obstructive pulmonary disease (COPD): Hospitalizations and ER Visits among US Medicare Beneficiaries. (31st December 2020) - Wang, Ping; Hassan, Mariam; Chatterjee, Anjan
Abstract: Background: NTMLD is a rare mycobacterial infection characterized by worsening lung function and increased healthcare resource burden. Many patients with NTMLD have comorbid respiratory diseases such as COPD. Management of NTMLD in patients with COPD may not get adequate attention as clinical management of COPD is often prioritized. There is a lack of data quantifying the incremental burden of NTMLD among patients with COPD. We assessed the incremental burden of NTMLD in patients with comorbid COPD by comparing their healthcare resource utilization (HCRU), in terms of hospitalizations and emergency room (ER) visits, to matched COPD patients without NTMLD. Methods: A retrospective cohort study was conducted using the US Medicare claims database (2010-2017). COPD patients with NTMLD were matched 1:3 to COPD patients without NTMLD (controls) by age and gender. HCRU was assessed in terms of hospitalizations (all-cause, respiratory related and COPD related) as well as ER visits (with and without subsequent hospitalization) over a 12-month follow-up period. Incremental burden of NTMLD was assessed by comparing the HCRU between COPD patients with NTMLD and controls using univariate and multivariate analyses adjusting for baseline comorbidities. Results: A total of 4, 010 COPD patients with NTMLD were matched to 12, 030 controls. In univariate analyses, a significantly higher proportion of COPD patients with NTMLD had hospitalizations and ER visits compared to controls (Fig 1(A)); the number of hospitalizations and ER visits were also higher among patients with NTMLD (Fig 2(A)). This incremental burden was also reflected in subsequent multivariate analyses after adjusting for baseline comorbidities. As an example, respiratory-related hospitalizations in COPD patients with NTMLD had Odds Ratio of 2.5 (95%CI 2.2-2.7) and Incident Rate Ratio (IRR) of 2.3 (95%CI 2.1-2.4) compared to controls (Fig 1(B), 2(B)). Figure 1: Proportion of Patients (A) and Odds Ratio (B) of Hospitalizations and ER Visits over a 12-month follow-up period among COPD patients with NTMLD vs. matched COPD patients without NTMLD. Figure 2: Per Patient Rate (A) and Incidence Rate Ratio (B) of Hospitalization and ER Visits over a 12-month follow-up period among COPD patients with NTMLD vs. matched COPD patients without NTMLD. Conclusion: COPD patients with NTMLD have a significantly higher disease burden due to hospitalizations and ER visits compared to COPD patients without NTMLD. These findings suggest the substantial incremental burden that NTMLD adds to existing COPD in patients and highlight the urgent need for attention and appropriate management. Disclosures: Ping Wang, PhD, Insmed Incorporated (Employee) Mariam Hassan, PhD, B. Pharm, Insmed Incorporated (Employee) Anjan Chatterjee, MD, MPH, Insmed Incorporated (Employee)